Successful neutrophil engraftment supported by granulocyte transfusion in adult allogeneic transplant patients with peri-transplant active infection. (December 2022) - Ikegawa, Shuntaro; Fujii, Nobuharu; Fujii, Keiko; Kimura, Maiko; Matsuda, Masayuki; Kondo, Takumi; Fujiwara, Hideaki; Asada, Noboru; Ennishi, Daisuke; Nishimori, Hisakazu; Matsuoka, Ken-ichi; Maeda, Yoshinobu
Abstract: Active infection at the time of allogeneic hematopoietic stem cell transplantation (HSCT) is a risk for non-relapse mortality (NRM) after HSCT. Granulocyte transfusion (GTX) has been used to prevent or treat life-threatening infections in patients with severe neutropenia. However, data are limited on the clinical benefits of GTX during HSCT. We retrospectively analyzed the transplant outcomes of HSCT patients who had undergone GTX between 2012 and 2020. Altogether, 20 patients with documented infection had received 55 GTXs during HSCT. No adverse events were observed during the GTX infusion. The average number of granulocytes was 0.40 (range, 0.10–1.59) × 10 9 /kg. The median neutrophil increment one day after GTX was 515 (range, −6 to 6630)/μl, which was significantly correlated with the infused granulocyte dose (p = 0.0007). A total of 17 of 20 patients achieved neutrophil engraftment. The number of infused granulocytes tended to higher in clinical responders (p = 0.12), and patients receiving ≥ 0.5 × 10 9 /kg showed trend toward to better transplant outcomes (GTX-high vs. GTX-low, 1-year OS; 33% vs. 11%, p = 0.19. 1-year NRM; 44% vs.77%, p = 0.11). The type of red blood sedimenting agents was significantly correlated with the amounts of granulocyte collection. In conclusion, GTX, especially with a high amount of containing granulocytes, could be a safe bridging therapy for neutrophil engraftment after HSCT in patients with active infection.